A highly elastic self-charging power system for simultaneously harvesting solar and mechanical energy. (November 2019) - Song, Weixing; Yin, Xing; Liu, Di; Ma, Weiting; Zhang, Maoqing; Li, Xinyuan; Cheng, Ping; Zhang, Chunlei; Wang, Jie; Wang, Zhong Lin
Abstract: Developing lightweight, flexible and sustainable power sources is desirable and favorable for wearable electronics with the rapid advancement of portable devices. Here, a highly elastic and sustainable power source is fabricated for harvesting and storing energy simultaneously from ambient sunshine and human movement. Flexible fiber-shaped dye-sensitized solar cells are smartly integrated with triboelectric nanogenerators and serve as generating set. The supercapacitors as energy storage devices can store direct current energy for the solar cells and alternating current energy from the triboelectric nanogenerators after rectified at the same time. Furthermore, the supercapacitors are easily integrated with generating set due to the same electrode materials with triboelectric nanogenerators. Due to the all flexible devices, the size of the whole power system can be easily tuned and connected with electronic devices to create self-powered wearable electronics. Graphical abstract: A highly stretchable, wearable and comfortable self-charging power system is fabricated to individually or simultaneously harvest solar energy from ambient light and mechanical energy from human movement. These energies are stored in supercapacitors to sustainably power wearable electronics. The charging time of the FDSSCs for supercapacitors is shortened by integrating the TENG which can exploit random body motion energy and provide an electronic output.Image 1 Highlights: Our findings establish optimization methodologies for combining direct current energy and alternating current energy. The dye-sensitized solar cells and triboelectric nanogenerator can independently and simultaneously charge a supercapacitor. The highly integrated device provides a possible way to realize a self-powered system in wearable electronics.